Second Hematopoietic Stem Cell Transplantation for Post-Transplantation Relapsed Acute Leukemia in Children: A Retrospective EBMT-PDWP Study - Yaniv, Isaac; Krauss, Aviva C; Beohou, Eric; Dalissier, Arnaud; Corbacioglu, Selim; Zecca, Marco; Afanasyev, Boris V; Berger, Massimo; Diaz, Miguel Angel; Kalwak, Krzysztof; Sedlacek, Petr; Varotto, Stefania; et al. (Biology of blood and marrow transplantation, 2018)
Outcome data were collected from the European Society for Blood and Marrow Transplantation registry on 373 children from 120 centers with relapsed leukemia (214 with acute lymphoblastic leukemia [ALL] and 159 with acute myelogenous leukemia [AML]) who underwent second allogeneic hematopoietic stem cell transplantation (HSCT) between 2004 and 2013. Overall survival (OS) was 38% at 2 years and 29% at 5 years, and leukemia-free survival (LFS) was 30% at 2 years and 25% at 5 years. Median follow-up after second HSCT was 36.4 months in the ALL group and 50.2 months in the AML group. In the ALL group, OS was 43% at 2 years and 33% at 5 years, and LFS was 34% at 2 years and 31% at 5 years. In the AML group, OS was 32% at 2 years and 24% at 5 years, and LFS was 24% at 2 years and 17% at 5 years. The 2-year nonrelapse mortality (NRM) rate was 22% in the ALL group and 18% in the AML group. Favorable prognostic factors (P < .05) for OS and LFS included >12 months between transplantations and chronic graft-versus-host disease after the first HSCT (in both groups), complete response before the second HSCT (ALL group only), and age >12 years (AML group only). Findings were more consistent over time in the ALL group, with no significant differences between 2-year and 5-year rates of relapse, NRM, and LFS. Children with relapsed acute leukemias have a substantial likelihood of long-term survival following second HSCT. Given the many novel targeted and immunomodulation therapies currently under development, it is important to identify specific patient subpopulations that may benefit from a second HSCT compared with those better suited to new approaches.
Keywords: analýza přežití; reoperace; Retrospective Studies; Survival Analysis; Prognosis; mladiství; akutní lymfatická leukemie; Relapse pediatric acute leukemia; mužské pohlaví; nemoc štěpu proti hostiteli; Leukemia, Myeloid, Acute; recidiva; Reoperation; dítě; Child; Second HSCT; Child, Preschool; Hematopoietic Stem Cell Transplantation; ženské pohlaví; prognóza; transplantace hematopoetických kmenových buněk; retrospektivní studie; předškolní dítě; Graft vs Host Disease; Humans; Recurrence; cGVHD; akutní myeloidní leukemie; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Female; Adolescent; lidé; Male